(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2026)
Background: Coronary artery disease (CAD) is a common heart disease that ranks as the leading cause of death and morbidity worldwide. Objectives: This study is designed to evaluate the levels of Anti-Aging Klotho and Apolipoprotein E4(APOE4) in the serum of CAD patients and their correlation with established Alzheimer’s disease biomarkers, Amyloid-β42 (Aβ42) and Phosphorylated-tau protein (P-tau). Method: In a case-control study, included two groups, the first group was 60 adult males in the age group 40-80 years, who were clinically diagnosed with CAD by a cardiologist, and the second group was 30 adult males who looked healthy. These assessments were conducted through the measurement of Klotho, Aβ42, P-tau protein, and APOE4. Results: Serum Klotho levels did not differ between CAD and the control group. In contrast, the mean level of APOE4 in CAD patients increased significantly compared to healthy individuals. Klotho was significantly and positively related to the Aβ42, P-tau protein, and APOE4. Binary logistic regression showed that P-tau protein and APOE4 were negatively associated with CAD (as a risk factor) and performed better in predicting CAD compared with the control group. Conclusion: The positive relationship of Klotho with Aβ42 and P-tau implies that higher Klotho levels might be connected to the regulation or response to neurodegenerative changes and aging-related processes. Higher Klotho levels reduce the odds of having CAD, identifying it as a protective factor, while P-tau and APOE4 are risk factors.